2020
DOI: 10.7759/cureus.10811
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Impact of Bariatric Surgery in Women With Polycystic Ovary Syndrome

Abstract: Polycystic ovarian syndrome (PCOS) is the most common endocrine disorder in reproductive-age women that causes infertility. Obesity and insulin resistance are closely tied to the pathophysiology of PCOS. Current first-line treatments include lifestyle modifications, hormone modulators, and laparoscopic ovarian drilling, but little attention has been given to bariatric surgery as a viable option. A detailed review of the literature regarding the outcomes of obese women with PCOS after bariatric surgery is neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…However, these improvements were associated with post-operative complications such as anastomotic ulcer, malnutrition, and gastrointestinal bleeding. Parallel to our findings, Lee et al (2020) reported a significant weight loss, improvement of hyper-insulinemia and hyperandrogenism, ovulatory function and menstrual regularity one year after bariatric surgeries.…”
Section: Discussionsupporting
confidence: 89%
“…However, these improvements were associated with post-operative complications such as anastomotic ulcer, malnutrition, and gastrointestinal bleeding. Parallel to our findings, Lee et al (2020) reported a significant weight loss, improvement of hyper-insulinemia and hyperandrogenism, ovulatory function and menstrual regularity one year after bariatric surgeries.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, neuroregulation of the hypothalamic-pituitary-ovarian axis is severely disturbed, and these factors affect the occurrence and progression of PCOS at multiple levels ( 52 , 53 ). Although PCOS is known to improve with weight loss and that weight loss is effective in restoring IR, hyperandrogenism, and the hypothalamic-pituitary-ovarian axis ( 54 56 ), there is a possible weight-loss-independent mechanism for PCOS improvement after metabolic surgery. Eid et al.…”
Section: Discussionmentioning
confidence: 99%
“…There has been existing reviews and meta-analyses with the same topic ( 15 , 35 , 56 ). However, it did not impair the innovation or value of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest that bariatric surgery in some PCOS women effectively improves ovulation, insulin resistance, hyperandrogenism, and hirsutism. In several obese PCOS patients, a regular menstrual cycle is restored after bariatric surgery [23]. Undoubtedly, bariatric surgery leads to weight loss and therefore results in resumed ovulation and pregnancy.…”
Section: Bariatric Surgerymentioning
confidence: 99%